Perbandingan dan Efek Populasi Ikan di Pantai Bunder Desa Bangsring Kecamatan Wongsorejo Kabupaten Banyuwangi - Abdur Rohman Wahid; Nour Athiroh Abdoes Sjakoer; Ari Hayati (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2023)
Bangsring Beach has the potential of unique marine natural resources and beautiful beaches. Underwater sea. Bangsring Beach also has rides that are played by visitors, one of which is snorkeling, Bangsring beach itself has several snorkeling sports while there are sprots that are often visited and rarely come, so that visitors or snorkelers have not yet enjoyed the sport that is not often visited a visitor. The purpose of this study is to study fish among the sports that are frequently visited by visitors and which are not frequented by visitors and anthropogenic activities also make the fish needed in these two sports increasingly lost. The method I use uses a simple technique which determines the station that I pick is determined by myself because the stations that depend on it are rarely visited by visitors. The results of this study found 29 species between the two sports that have been determined. To reduce the fish in Bangsring Beach due to unexpected environmental changes and the activities of visitors who step on coral reefs and make dead coral make suitable fish on Bunder beach.